2019
DOI: 10.1111/faf.12401
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Columbian fisheries catch reconstruction for a subtropical estuary in South America

Abstract: Small‐scale fisheries provide food and livelihoods for thousands of people along the Brazilian coastline. However, considerable uncertainties still surround the extent to which artisanal and subsistence fisheries contribute to the total of national landings and their historical ecological significance. Fisheries monitoring is deficient in Brazil, and historical records are limited to irregular accounts spanning the last few decades, while this coastline has supported human populations for at least 6,000 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 66 publications
(97 reference statements)
0
28
0
7
Order By: Relevance
“…A estimativa da densidade de NMI por M 3 dos peixes ósseos, por sua vez, colabora com uma interessante informação sobre a demografia do assentamento. Seguindo o exemplo dos cálculos aplicados por Fossile et al (2019), é possível estimar que os animais processados no Rio do Meio foram consumidos por um total de 3.384 pessoas ao longo dos dois séculos de sua ocupação. A densidade se aproxima mais dos dados obtidos para Cubatão I por Fossile et al (2019), do que dos dados obtidos por Klokler (2008) para Jabuticabeira II.…”
Section: Comentários Finaisunclassified
See 2 more Smart Citations
“…A estimativa da densidade de NMI por M 3 dos peixes ósseos, por sua vez, colabora com uma interessante informação sobre a demografia do assentamento. Seguindo o exemplo dos cálculos aplicados por Fossile et al (2019), é possível estimar que os animais processados no Rio do Meio foram consumidos por um total de 3.384 pessoas ao longo dos dois séculos de sua ocupação. A densidade se aproxima mais dos dados obtidos para Cubatão I por Fossile et al (2019), do que dos dados obtidos por Klokler (2008) para Jabuticabeira II.…”
Section: Comentários Finaisunclassified
“…Seguindo o exemplo dos cálculos aplicados por Fossile et al (2019), é possível estimar que os animais processados no Rio do Meio foram consumidos por um total de 3.384 pessoas ao longo dos dois séculos de sua ocupação. A densidade se aproxima mais dos dados obtidos para Cubatão I por Fossile et al (2019), do que dos dados obtidos por Klokler (2008) para Jabuticabeira II. No entanto, não é possível realizar comparações com os dados dos trabalhos citados, uma vez que representam assentamentos de natureza e tempo de ocupação totalmente distintos.…”
Section: Comentários Finaisunclassified
See 1 more Smart Citation
“…These consisted of 180 samples from non-ceramic contexts (n = 12) and 88 samples from ceramic contexts (n = 5), located in coastal areas (estuaries, bays, lagoons and coastal sand barriers) between latitudes 22.9°S and 28.5°S (Supplementary information 2). Non-ceramic contexts (Enseada I, Armação do Sul, Cabeҫuda, Espinheiros II, Forte Marechal Luz, Jabuticabeira II, Laranjeiras I, Morro do Ouro, Piaçaguera, Rio Comprido, Zé Espinho, Casa de Pedra) had modelled radiocarbon dates between 5950 − 5550 (Casa de Pedra 22 ) and 1300 − 500 cal BP (Forte Marechal Luz 58 ), while ceramic contexts (Enseada I, Forte Marechal Luz, Galheta IV, Laranjeiras II, Praia da Tapera) had radiocarbon dates ranging between 1200 − 900 (Enseada I 36,47 ) and 750 − 500 cal BP (Galheta IV 28 ) at 95.4% probability. The δ 13 C and δ 15 N values were mostly produced on bone collagen of individuals of distinct sexes and ages (n = 222), followed by dentine collagen (n = 46), in some cases from individuals whose bone collagen had also been analyzed (e.g.…”
Section: Review Of Human and Faunal Stable Isotopes Valuesmentioning
confidence: 99%
“…Sambaquis were concentrated around resource-rich coastal environments (bays, estuaries and lagoons), where relatively abundant and predictable aquatic resources offered conditions for the establishment of dense and stable populations, potentially with similar or shared cultural identities in some areas 11,12,15,20,21 . Studies have demonstrated that several large shell mounds were occupied for extensive periods of time 22,23 as collective or community-based cemeteries with enduring political and ideological values 11,12,15,24 . Parallel to these large sites, smaller and shallower sites similarly offer faunal remains depicting a high degree of dependence on aquatic resources 16-19,25−29 .…”
Section: Introductionmentioning
confidence: 99%